Collaboration and Technology 17th International Conference, CRIWG 2011, Paraty, Brazil, October 2-7, 2011. Proceedings - Vivacqua, Adriana S.; Gutwin, Carl; Borges, Marcos R. S. (Springer eBooks., 2011)
This book constitutes the proceedings of the 17th Collaboration Researchers' International Working Group Conference on Collaboration and Technology, held in Paraty, Brazil, in October 2011. The 12 revised papers presented together with 6 short papers were carefully reviewed and selected from numerous submissions. They are grouped into four themes that represent current areas of interest in groupware research: theoretical foundation, empirical studies, methods and techniques, and tools for communication and cooperation.